Сучасні методи оцінки персоналу у системі управління людськими ресурсами - Шматько, Наталія Михайлівна; Кармінська-Бєлоброва, Марина Володимирівна; Пантелєєв, Михайло Сергійович (Таврійський національний університет ім. В. І. Вернадського, 2024)
У сучасній ринковій економіці, коли конкуренція між підприємствами постійно зростає, роль персоналу в успіху самого підприємства стає критично важливою. Ефективне управління персоналом вимагає правильного підходу до процесів підбору, розвитку, навчання та мотивації працівників. Методи оцінки персоналу підприємства відіграють ключову роль у вирішенні цих завдань, допомагаючи виявити якості та потенціал своїх співробітників, необхідних для досягнення стратегічних цілей. У статті розглядаються сучасні методи оцінки персоналу підприємства, серед яких виділено: метод бальної оцінки в оцінці персоналу, метод анкетування, метод порівняння за парами, метод рейтингових поведінкових установок, метод 360 градусів, аssessment сenter, методи оцінки з урахуванням моделей компетенцій. У сучасних умовах проблема оцінки персоналу стає актуальною, так як людський ресурс відіграє все більш важливу роль у конкурентоспроможності підприємства над ринком. При формуванні системи оцінки персоналу в організації необхідно враховувати недоліки та переваги кожного з методів, для створення дійсно ефективного процесу оцінки, який даватиме результат.

Evaluation of enterprise employees is one of the management functions personnel aimed at determining the level of effectiveness activities and obtaining the necessary information about human resources the organization as a whole. This is a mandatory element of the control system in any organization, the "end-to-end" type of personnel work is inevitably taken into account when development of personnel programs. Effective personnel assessment plays a huge role in management them, it is the basis of many procedures: hiring, internal transfers, layoffs, enrollment in the reserve for promotion, material and moral incentives, application of sanctions, retraining and advanced training, personnel control, improving the organization of managerial work, techniques and methods work, improving the structure of the apparatus. Lack of reliable systems assessments may cause the organization to lose a capable employee and acquire an incapable. There is a wide variety of methods, each of which is unique in its own way, and the organization faces a great challenge in determining the appropriate one both for the company as a whole and for its individual parts. The article discusses modern methods of assessing enterprise personnel, among which the scoring method in personnel assessment, the questionnaire method, the method of comparison in pairs, the method of rating behavioral settings, the 360 degree method, assessment center, assessment methods taking into account competency models are highlighted. Organizations often combine or modify methods and adjust them to suit themselves, taking into account financial costs and specifics organizations. Only by taking into account all the listed subtleties can you build your system for personnel assessment and at the same time achieve effective use of human resources. A variety of personnel assessment methods allows the employer to identify current and potential staff capabilities, see the strengths and weaknesses of the system management and create your own employee assessment model based on the specifics and goals of the organization. All these necessary measures contribute to economic stability, increased efficiency, labor productivity, cohesion and mutual assistance of employees, mentoring and, most importantly, a caring attitude towards development priorities and strategies the organization in which they work.
Modern methods of personnel evaluation in the human resource management system
Keywords: система управління персоналом; критерії оцінки персоналу; методи оцінки; метод 360 градусів; аssessment сenter; personnel assessment; personal approach; method; standard estimates questionnaire method